Mycobiome of Fraxinus excelsior With Different Phenotypic Susceptibility to Ash Dieback - Agostinelli, Marta; Nguyen, Diem; Witzell, Johanna; Cleary, Michelle (Frontiers in Forests and Global Change, 2021)
For the last two decades, large-scale population decline of European ash (Fraxinus excelsior) has occurred in Europe because of the introduction of the alien fungal pathogen, Hymenoscyphus fraxineus, from East Asia. Since European ash is a keystone species having critical importance for biodiversity, and only a small percentage of the ash population appears to show some tolerance against the pathogen, the loss of ash trees means that other associated organisms, especially those with high or obligate associations to ash, are at risk of further species declines. In this study, we used high throughput DNA sequencing and multivariate analysis to characterize: (i) the mycobiome in aerial tissues (i.e., leaf, bark, and xylem) of ash trees showing different phenotypic response to ash dieback, (ii) the temporal variation in fungal communities across the growing season, and (iii) the similarity in fungal community structure between ash and other common trees species that may serve as an ecological niche substitute for ash microfungi. Results showed that fungal communities differed among the three tissue types, susceptibility classes, in time and between sites. Trophic analysis of functional groups using the FUNGuild tool indicated a higher presence of pathotrophic fungi in leaves than in bark and xylem. The share of pathotrophic fungi increased along a gradient of low to high disease susceptibility in both bark and xylem tissue, while the proportion of symbiotrophic fungi correspondingly decreased in both tissue types. Neighboring, alternative host trees did not share all the fungal species found in ash, however, most microfungi uniquely associated to ash in this study are generalists and not strictly host specific. The progressive disappearance of ash trees on the landscape imposes a high risk for extinction of Red-listed macrofungal species, and breeding for resistance against ash dieback should help sustain important biodiversity associated to ash. Microfungal diversity though may be less prone to such demise since most ash-associated endophytes appear to occur on a broad range of host species.